2023
DOI: 10.1002/jsp2.1267
|View full text |Cite
|
Sign up to set email alerts
|

The influence of intervertebral disc overloading on nociceptor calcium flickering

Abstract: IntroductionMechanical overloading can trigger a degenerative‐like cascade in an organ culture of intervertebral disc (IVD). Whether the overloaded IVD can influence the activation of nociceptors (i.e., the damage sensing neurons) remains unknown. The study aims to investigate the influence of overloaded IVD conditioned medium (CM) on the activation of nociceptors.MethodsIn the static loading regime, force‐controlled loading of 0.2 MPa for 20 h/day representing “long‐term sitting and standing” was compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The IVD organ culture bioreactor has long been used in basic and translational research for its advantages of precise control in biochemical and biomechanical aspects and is an indispensable tool for bridging in vitro and in vivo models 13,31,32 . Salzer et al observed an increase in the metabolic activity of NP tissue with dynamic loading, coupled with a notable reduction in living cell density by the seventh day 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IVD organ culture bioreactor has long been used in basic and translational research for its advantages of precise control in biochemical and biomechanical aspects and is an indispensable tool for bridging in vitro and in vivo models 13,31,32 . Salzer et al observed an increase in the metabolic activity of NP tissue with dynamic loading, coupled with a notable reduction in living cell density by the seventh day 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In a disc‐like organ model, Gewiess illustrated that extended static loading resulted in a 12.1% reduction in cell viability in the annulus fibrosus (AF) and a 4.2% reduction in the nucleus pulposus (NP). Conversely, dynamic loading had no discernible impact on cell viability in the disc 31 . Salzer et al proposed that dynamic loading acts as an additional stressor, leading to a decrease in nucleus pulposus (NP) cell density 33 .…”
Section: Discussionmentioning
confidence: 99%
“…This threshold value has been shown to successfully exclude noise based on our former calcium flickering evaluations in dead neurons. [ 57 ] The capsaicin induced peak height was calculated by subtracting the maximum ΔF / F 0 after adding capsaicin by an average value of ΔF / F 0 over a time window (500 time frames) before capsaicin was added.…”
Section: Methodsmentioning
confidence: 99%